Bilateral cleft lip repair - advantages of pfeifer's technique - Yaratha Sivanagendra Reddy; Rayadurgam Venkata Kishore Kumar; Devireddy Sathya Kumar; Gali Rajasekhar; Vaka Ramesh Babu; Kanubaddy Sridhar Reddy; Kuruganti Prasanna Purna (Wolters Kluwer Medknow Publications, 2018)
Context: Primary repair of bilateral cleft lip depends on the sound knowledge of anatomy, identification of landmarks, clinical variation of presentation, surgical expertise of the operator, etc., Herewith, we present the results of 129 cases performed during our study. Aim: To evaluate the advantages of Pfeifer's technique in bilateral cleft lip repair. Design: This was a retrospective analysis of the results of repair. Patients and Methods: The study was carried out on 129 patients using Pfeifer's technique. Pfeifer described a technique which involves changing the lip skin incision to a wavy line, thus making it less conspicuous, using the concept of "morphological order." The basis of this technique is, a skin incision between two points can be lengthened if both points are joined in a curved or wavelike manner rather than in a straight line. Results: Lip parameters improved by 70% as viewed in frontal profile in terms of white roll match, vermilion match, and Cupid's bow. Nasal parameters improved by 80% as viewed in basal view in terms of alar symmetry, nasal dome and alar base. Conclusions: We found four advantages by strict adherence to the steps in the technique as given in the available literature. This technique is easy to learn and teach with satisfactory results.